Gender and Motivational Orientations in Second Language Acquisition: Indonesian Undergraduates - Ismail; Rusdin; Norzanita Othman (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Although gender differences in motivation to learn English have been widely investigated, findings remain inconsistent, particularly in the Southeast Asian context. Limited research has explored how male and female Indonesian students differ in their integrative and instrumental motivational orientations, especially within international learning settings. Therefore, this study aims to examine the relationship between gender and motivational orientations; integrative and instrumental towards English learning among Indonesian undergraduate students at Universiti Utara Malaysia. A total of 89 students from various academic fields participated in a survey using a modified version of Gardner’s Attitude/Motivation Test Battery (AMTB, 2004) comprising 20 items. The findings revealed that both male and female students showed high motivation in learning English, with males slightly more motivated than females. While female students demonstrated stronger integrative motivation and males stronger instrumental motivation, these differences likely reflect distinct social and learning orientations. The results suggest that in an English Medium Instruction (EMI) environment, both genders recognise English as essential for academic and professional success. Pedagogically, teachers should design activities that accommodate both motivational orientations—integrative tasks that promote interaction and cultural awareness for female learners, and instrumental tasks related to career goals for male learners. Understanding these orientations enables educators to create more balanced and motivating learning experiences. Future studies should further investigate how motivational orientations relate to learners’ English proficiency and academic achievement.